Analysis of Service Quality and Product Quality on Customer Purchase Decisions in CV. Surya Indah Jaya Medan with Price as a Variable Intervention - Reiwines Reiwines; Ferry Hidayat (Institute of Computer Science (IOCS), 2022)
This study aims to determine the effect of service quality and product quality on customer purchase decision in CV. Surya Indah Jaya Medan with price as a variable intervention. This type of research is explanatory research. The population in this study were all customers of CV. Surya Indah Jaya, totaling 7,311 customers. The technique of determining the sample is to use the 10% significant slovin technique so that as many as 99 samples are obtained. In the study which will be distributed with questionnaires measured by a Likert scale. The data analysis used multiple linear regression analysis and the coefficient of determination as well as simultaneous test and partial test. The results showed that service quality and product quality have a significant effect on customer purchase decision in CV. Surya Indah Jaya Medan with price as a variable intervention.